Effects of a Job Crafting Intervention Program on Work Engagement Among Japanese Employees: A Randomized Controlled Trial - Sakuraya, Asuka; Shimazu, Akihito; Imamura, Kotaro; Kawakami, Norito (Frontiers in Psychology, 2020)
Objective: The current randomized controlled trial investigated the effectiveness of a job crafting intervention program on work engagement as the primary outcome and job crafting as the secondary outcome among Japanese employees. Methods: Participants who met the inclusion criteria were randomly assigned to an intervention group (n = 138) or a control group (n = 143). The job crafting intervention program provided only to the intervention group consisted of two 120-minute group sessions with e-mail or letter follow-up. Outcomes were assessed at baseline and at 3-month and 6-month follow-up in both groups. Results: In the total sample, the job crafting intervention program showed a non-significant effect on work engagement at both 3-month and 6-month follow-up. Also, job crafting did not improve significantly. However, the program showed a significant intervention effect on work engagement (p = 0.04) with small effect size (Cohen’s d = 0.33 at 3-month follow-up) of workers in a lower job crafting subgroup. Conclusions: The job crafting intervention program may not be sufficiently effective to improve work engagement and job crafting for the entire sample of participants. However, it may be effective for workers in lower job crafting subcategories. Trial Registration: UMIN Clinical Trials Registry (UMIN-CTR) (ID = UMIN000026668).